Autoestima y Calidad de Vida en Personas con Diabetes. Hospital Regional Docente de Trujillo, 2017 - Guerrero Vergaray, Ana María (2017)
Quantitative, descriptive, correlational, cross-sectional study aimed at establishing the relationship between self-esteem and quality of life in people with diabetes, in the HRDT. Concepts of self-esteem were considered according to Coopersmith (1967) and quality of life according to WHO (1996). The sample was 124 people with diabetes. The instruments used were the self-esteem inventory of Coopersmith adults version and the questionnaire of specific quality of life for diabetes mellitus (EsDQOL). For the data analysis the gamma statistical test was applied in the SPPS version 24 program. The results showed that 94.4% of people with diabetes had a mean level of self-esteem, 4.8% high level and 0.8% low level. On the assessment of the dimensions of quality of life: in the satisfaction with the treatment, 70.2 porcent presented high level of satisfaction; In the impact of treatment, 79 porcet presented low impact level. For the social-vocational concern, 96.8 porcent presented low level of concern and for the dimension of concern related to diabetes, 51.6 porcent presented low level of concern. When correlating the variables, it was verified that only satisfaction with the treatment is significant related to the self-esteem (-p = 0.011).